不知道第一题是否如下,因为有一些不清楚:
1.2004÷(1998×1998-(1998-1))/(1998×1998-1998×1997+1997×1997)
= 2004÷(1998×1998-(1998-1))/(1998×1998-(1997+1)×1997+〖1997〗^2 )
= 2004÷(1998×1998-(1998-1))/(1998×1998-〖1997〗^2-1997+〖1997〗^2 )
= 2004÷(1998×1998-1997)/(1998×1998-1997)
= 2004÷1
= 2004
2.(1+1/3 + 1/5+1/7)×(1/3+1/5+1/7+1/9)-(1+1/3+1/5+1/7+1/9)×(1/3+1/5+1/7)
= (1/3+1/5+1/7+1/9)×1+(1/3+1/5+1/7+1/9)×(1/3+1/5+1/7)-(1/3+1/5+1/7)×1-(1/3+1/5+1/7+1/9)×(1/3+1/5+1/7)
= (1/3+1/5+1/7+1/9)-(1/3+1/5+1/7)
= 1/3+1/5+1/7+1/9-1/3-1/5-1/7
= 1/9